Metode Kopertif Tipe Jigsaw Terhadap Hasil Belajar Siswa Pada Bidang Studi Fiqih Kelas VIII DI MTS HJ. Siti Julia Secanggang Tahun Ajaran 2021-2022 - Ishak, Ali Mukhlis, Zaifatur Ridha (ALACRITY : Journal of Education, 2022)
Learning at MTs Hj . Siti Julia Secanggang this part big still use old method ie lecture , memorization and sometimes ask answer , if Thing this going on continously so can make participant educate bored in learn , if no there is variation method so participant educate will feel fed up accept lessons and _ Thing this is what causes participant educate no concentration , drowsiness and even sleep in in class moment lesson still going on , conditions thereby must quick overcome with change in teach , if before participant educate only come , sit down and shut up , then moment here it is participant educate must truly involved in process learning . Method jigsaw learning is wrong one method where participant educate in place to in team study heterogeneous up to five members six people . Various Theory academic served to participant educate in form text , and every participant educate responsible answer for learn one portion the material .With apply method learning this expected participant educate have experience new in learn , as well could reach destination the learning in expect , because destination from learning that on the main thing is is reach competencies that have set , by because that various type method and strategy need used for participants educate no feel fed up with learning the . The method used in this study is a quantitative method, with the aim of knowingHow InfluenceMethod Cooperative Jigsaw Type Against Results Study Student on Field Studies Jurisprudence Class VIII at MTs Hj . Siti Julia Secanggang Year 2021-2022.